A Model for Poverty Reduction in the Developing World (International Journal of Medicine and Medical Sciences, 2011)
In 2007, 230 scientific journals collaborated in calling attention to the critical problem of poverty. In 2002, the United Nations’ Secretary General underscored the connection between poverty and human development by commissioning the Millennium Project to reverse poverty and eradicate the hunger and disease that afflict billions of people throughout the world. These parallel occurrences in different sectors of society argue for the same action: the plight of the poor must be addressed and innovative models for poverty reduction must be considered for implementation.